OPTICAL PROPERTY STUDY OF GaN THIN FILMS GROWN BY UNBALANCED MAGNETRON DC SPUTTERING METHOD - (NIM 20298516), MUNASIR
The Gallium Nitrida (GaN) thin films have been grown onto (0001) sapphire substrate by Unbalanced Magnetron DC Sputtering Method. The range of deposition temperature was 630-740oC, and Argon and Nitrogen gas of flow rates were witted. Study of optical properties of GaN thin film by photoluminescence (PL) at room temperature, and obtain that deposition temperature strongly influence to PL spectrum intensity, its increase with increased deposition temperature, sugest that GaN thin film to be more best quality. From PL measuring , we obtain that GaN thin films, have optical bandgap of- 3,4 eV and the dominant luminescence occur of blue zone (blue luminescence) Ep - 2,7 eV. FWHM of GaN thin film is - 0,421 eV at deposition temperature of 740oC .